SHOULD ROUTINE LIVER BIOPSY BE CONSIDERED IN BARIATRIC SURGICAL PRACTICE? AN ANALYSIS OF THE LIMITATIONS OF NON-INVASIVE NAFLD MARKERS - CONCON,Matheus Mathedi (2022)
ABSTRACT Background Non-invasive markers are useful and practical tools for assessing non-alcoholic fatty liver disease (NAFLD), but liver biopsy remains the gold-standard method. Liver biopsy can be easily obtained on individuals undergoing bariatric surgery, but there is no ultimate evidence on the relationship between costs, risks and benefits of its systematic performance. Objective To compare the diagnostic accuracy of non-invasive methods with liver biopsy for detection and staging of NAFLD in obese individuals undergoing bariatric surgery. Methods This is a cross-sectional, observational and descriptive study which enrolled individuals who underwent bariatric surgery from 2018 through 2019 at a public tertiary university hospital. Ultrasound scan, hepatic steatosis index, Clinical Non-Alcoholic Steatohepatitis Score (C-NASH), hypertension, alanine aminotransferase (ALT) and insulin resistance (HAIR), aspartate aminotransferase (AST) to Platelet Ratio Index (APRI), NAFLD Fibrosis Score (NFS) and body mass index, AST/ALT ratio, and diabetes (BARD) were the methods compared with the histopathological examination of wedge liver biopsies collected during surgery. Results Of 104 individuals analyzed, 91 (87.5%) were female. The mean age was 34.9±9.7 years. There was no biopsy-related morbidity. The respective overall accuracies of each marker analyzed were: ultrasound scan (79.81% for steatosis), hepatic steatosis index (79.81% for steatosis), HAIR (40.23% for steatohepatitis), C-NASH (22.99% for steatohepatitis), APRI (94.23% for advanced fibrosis), NFS (94.23% for advanced fibrosis), and BARD (16.35% for advanced fibrosis). Discussion Given the high prevalence of liver disease within this population, even the most accurate markers did not present enough discretionary power to detect and/or rule out the NAFLD aspects they were designed to assess in comparison with liver biopsy, which is safe and easy to obtain in these patients. Conclusion Wedge liver biopsy during bariatric surgery helps to diagnose and stage NAFLD, presents low risks and acceptable costs; given the limitations of non-invasive methods, it is justifiable and should be considered in bariatric routine.